Analysis of Business Financing of Capture Fishermen from Non-Formal Sources in Kuala Indragiri Sub-District, Indragiri Hilir District, Riau Province - Arsad Alansyah Harahap; Lamun Bathara; Eni Yulinda (Faculty of Fisheries and Marine, Universitas Riau, 2024)
Funding for fishermen's enterprises refers to the costs fishermen require to procure investment goods and operational costs for fishing activities. Funding for fishermen's enterprises is sourced from various channels. This research was conducted in May 2024 in Kuala Indragiri District, Indragiri Hilir Regency, Riau Province. The research has two objectives: first, to describe the procedures for funding fishermen's enterprises. The second objective is to determine the influence of funding procedures and the socio-economic conditions of fishermen on the decision to borrow from non-formal sources. The sample consisted of 79 fishermen from 3 villages selected using the purposive sampling. Data collection was done through interviews, documentation, and questionnaires. Data analysis was conducted using Descriptive Analysis and Multiple Linear Regression. The results of the descriptive analysis show that the procedures for funding fishermen's enterprises can be sourced from self-funding, family, and non-formal sources referred to as